A megújuló energiaforrások alkalmazása a villamosenergia és hőtermelésre I. Napenergia, szélenergia, vízenergia - Haffner, Tamás (Közép-Európai Közlemények, 2017)
Renewable energy sources can be used to generate electricity, heat energy and combined heat and power. Despite several technological and other barriers, use of renewable energy is constantly growing worldwide thus we can expect further expansion of renewable energy sources and the increase of their importance in energy supply. Utilisation of solar energy would be able to cover the total energy needs of the Earth but its low energy density, its high demand for space and the high investment costs of its use for power generation limit its use. At the same time, solar energy utilisation is the most innovative type of use of renewable energy sources, in relation to which numerous such innovative technical innovations were born recently or are developing that can support the prosperity of utilisation of solar energy. The usable wind energy potential of the Earth is 400,000 TJ/year, the exploitation of which would require 3 million wind turbines with 1 MW nominal power. The average life span of wind turbines is 30 years and their payback period is high, 7.1–21.9 years. Exploitable hydropower reserves of the Earth is 16,000–20,000 TWh, however the approximately 11,000 hydropower plants currently operating in the world are 3,000 TWh. The toolkit of hydropower utilisation is mature and proven, with low technical risk. However, it requires high investment costs but the life span of hydropower plants can exceed 100 years with proper maintenance.